2014
DOI: 10.4028/www.scientific.net/amr.935.224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Oxide on Fire Performance of Intumescent Fire Retardant Coating

Abstract: The objective of this research work was to study the thermal efficiency of intumescent fire retardant coating (IFRC) designed to protect structural steel in event of fire. IFRC has been effectively developed by using ammonium polyphosphate (APP), expandable graphite (EG), melamine (MEL), boric acid (BA), titanium oxide (TiO2), and bisphenol A BE-188 with polyamide amine H-2310 as curing agent. Six formulations were developed using different weight percentage (wt. %) of TiO2 and samples were tested for char exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Nanofillers, on reaction with phosphate, can induce a synergistic effect in IFRCs. The well-known synergist candidates reported to date included TiO 2 nanoparticles (NPs) [28] and SiO 2 NPs [29]. However, other types of nanofillers still need to be tested in order to identify their function in synergism for an intumescent scheme [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofillers, on reaction with phosphate, can induce a synergistic effect in IFRCs. The well-known synergist candidates reported to date included TiO 2 nanoparticles (NPs) [28] and SiO 2 NPs [29]. However, other types of nanofillers still need to be tested in order to identify their function in synergism for an intumescent scheme [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to make fire-retardant cotton fabric23. Most effective present-day fire-retardant materials use heavy metals4567 or bromine89-containing species to efficiently arrest fires. In the light of environmental and health concerns, and upcoming legislation restrictions regarding brominated fire retardants91011, it is thus very important to develop new procedures for intrinsically fire retardant bulk materials, as well as, for fire-retardant and fire-blocking coatings, at best using environmentally benign materials and processes1213.…”
mentioning
confidence: 99%
“…127 The best performance occurs when the atomic ratio between titanium and phosphorus is equal to 0.5 corresponding to the ratio observed in TiP 2 O 7 . Another study showed that 4% TiO 2 was optimum for the better thermal insulation properties of amine cured epoxy intumescent coatings 128…”
Section: Mineral Fillersmentioning
confidence: 99%